BLIND TEST GOLONGAN SENYAWA PSIKOTROPIKA DALAM SAMPEL URIN - Maharani, Gusti Ayu Kopang; Rismayani, Putu Ayu; Devi, Ni Nyoman Adhi Satvika; Winarni, Ni Putu Metha Pradnyandari Putri; Sari, Pande Made Nova Armita (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 9 No 2 (2019): Indonesian Journal of Legal and Forensic Sciences, 2019)
Cases of psychotropic abuse have occurred in Indonesia. Drug abuse or detrimental use is the use of psychotropic without medical supervision. The case of drug abuse is a case that requires forensic toxicology examination. Forensic toxicology examination consists of the stages of screening tests, confirmation tests, and interpretation of results. This study aims to determine the psychotropic compounds contained in urine samples. The screening test method used is the immunoassay technique using a strip test, the results obtained that urine samples show positive results on the barbiturate group test strips. Confirmation test method is done by TLC-Spectrophotodensitometry method, the results obtained that the barbiturate class compounds contained in the sample are phenobarbital compounds. Furthermore, a determination test was performed and the results were obtained that the levels of phenobarbital in urine in a 4 µl drop volume with replication 3 times were 22.97 ng / µl, 34.66 ng / µl, and 22.42 ng / µl.